2001
DOI: 10.1159/000048834
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus DNA and p53 Gene Mutations in Esophageal Cancer Samples and Adjacent Normal Mucosa

Abstract: Background/Aim: There is evidence of a possible etiological role of human papillomaviruses (HPVs) in the development of esophageal tumors. Loss of function of the wild-type p53 tumor suppressor gene product by binding to E6 oncoproteins of high-risk HPVs is considered an important event in tumor development. The aim of this study was to verify the prevalence of HPV infection and p53 mutation in esophageal tumor tissue samples and in the adjacent normal mucosa in patients from a high-risk area in Italy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…This finding is similar to several large series in the literature, where the reported rate of HPV positivity in oropharyngeal SCCs ranged from 47% to 72% [1,2,[4][5][6]. In line with these studies, we found that p16 is highly sensitive and specific for HR-HPV in the oropharynx, especially the tonsil [20,21,27]. These findings would seem to obviate the need for direct HPV testing, at least in the tonsil.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to several large series in the literature, where the reported rate of HPV positivity in oropharyngeal SCCs ranged from 47% to 72% [1,2,[4][5][6]. In line with these studies, we found that p16 is highly sensitive and specific for HR-HPV in the oropharynx, especially the tonsil [20,21,27]. These findings would seem to obviate the need for direct HPV testing, at least in the tonsil.…”
Section: Discussionsupporting
confidence: 92%
“…Although SCCs of the oropharynx are most strongly associated with HR-HPV infection, head and neck SCCs (HNSCCs) of other sites including SCCs of the sinonasal cavity, nasopharynx, oral cavity, and larynx have also been shown to harbor the virus, and HR-HPV has been demonstrated in several non-head and neck sites including lung and esophagus [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…126 In our series of 700 SCCs from China, of which 117 (16.9%) were HPV DNA positive, 11 HPV signals were detected in the surrounding hyperplastic and dysplastic epithelia in 5.6% of patients, and in the resection margins of 0.2% cases, figures that agree with another recent report. 118 The presence of HPV in the adjacent normal and dysplastic epithelium fits in with the "condemned mucosa" concept, recently proposed to explain the pathogenesis of multifocal HPV induced carcinogenesis in the genital tract and in the upper aerodigestive tract, 127 including oesophageal SCC. 10 124 …”
Section: Hpv Dna In Oesophageal Precancer Lesionssupporting
confidence: 60%
“…Accumulating evidence on the presence of HPV DNA in normal oesophageal epithelium (Chang et al, 2000;Zhou et al, 2003) and in cancer precursor lesions (Pillai and Nair, 2000;Astori et al, 2001) suggests an involvement of HPV in very early stages of the classical dysplasia -carcinoma sequence. The notion was also supported by the demonstration of HPV infection using serologic assays with enzyme-linked immunosorbent assays (ELISAs) (Han et al, 1996).…”
mentioning
confidence: 99%